Los Valores en la Familia y su Influencia en el Desempeño Académico de los Niños y Niñas de Tercer Grado de Educación General Básica, de la Escuela Municipal “Héroes del Cenepa” de la Ciudad de Loja y la Intervención del Trabajador Social, Período Lectivo 2015 – 2016 - Quevedo Ruiz, Laila Denisse (2016)
This research aims to contribute to the understanding of the issues raised; How inadequate practice of values affects the academic performance of children in the third grade of elementary general education of the Municipal School "Heroes Cenepa" city of Loja, in the 2015-2016 school period; to the respective research on the subject of study and reach their full compliance raised an overall objective; encourage the practice of values, to achieve good academic performance of children; the same that served as a guide to define the specific objectives. The specific objectives; support from theory and contextualize from fieldwork categories and variables of the problem, for compliance with the same information was sought about the categories of study as values, family, academics, children, general education basic and intervention social worker, who facilitated the completion of the review of the literature and know in depth the topic of study. The second specific objective set was to determine the causes and effects generated by improper practice of values inside the homes of the children, and how they influence academic performance; the same as was achieved with the results of the investigation; through surveys of parents, students and teacher interviews; where it was determined that in the home causes generated in children negative attitudes as there are: the lack of parental interest in fulfilling the tasks, the lack of rules in the home on monitoring activities spend time, demotivation by the student to study, leaving the student with no interest and responsibility for what you learn in school; thus directly affects academic performance; and therefore it proceeded to the fulfillment of the third objective; directed and designed a proposal aimed at strengthening family values, which will be operationalized by school authorities. 5 Family problems, domestic violence, inadequate communication methods practiced in homes and how they affect the school environment: In the process of research findings that influence the practice of values in children as found. Scientific and auxiliary methods as deductive, inductive, synthetic and statistician consisted of collecting information necessary for the investigative process through techniques and instruments that made possible the compilation of the different methods used for the implementation of field work, information and finally proceeded to developed the conclusions which mentions generally, if there is inadequate practice of values in children that affects academic performance and in terms of the recommendations is to let them know more about values and how to apply them in daily life.